The First-Night Effect in Elite Sports: An Initial Glance on Polysomnography in Home-Based Settings - Hof zum Berge, Annika; Kellmann, Michael; Jakowski, Sarah (Frontiers in Psychology, 2021)
Self-applied portable polysomnography is considered a promising tool to assess sleep architecture in field studies. However, no findings have been published regarding the appearance of a first-night effect within a sport-specific setting. Its absence, however, would allow for a single night sleep monitoring and hence minimize the burden on athletes while still obtaining the most important variables. For this reason, the aim of the study was to assess whether the effect appears in home-based sleep monitoring of elite athletes. The study sample included eight male and twelve female German elite athletes from five different sports. Participants slept with a portable polysomnography for two nights (in total), which they self-applied at night before going to bed. Time in bed and wake-up time in the morning were freely chosen by each individual athlete without any restrictions regarding time or sleeping environment. Participants were asked to keep the same location and time frame during the two days of monitoring and stick to their usual sleeping schedules. Sleep stages were manually scored using 30-second epochs. Sleep parameters and stages were later compared with the help of linear mixed models to investigate the factor time. Significant differences between the two nights were found for percentage of Non-REM sleep (T(19)=-2,10, p<.05, d=-0.47, 95%-CI [-7.23, -0.01]) with small effect size, Total Wake Time (T(19)=2.30, p=.03, d=0.51, 95%-CI [1.66, 35.17]), SE (T(19)=-2.48, p=.02, d=-0.55, 95%-CI [-7.43, -0.63]) and Wake percentage (T(19)=2.47, p=.02, d=0.55, 95%-CI [0.61, 7.43]) with moderate effect sizes, and N3 Sleep Onset Latency (T(19)=3.37, p < .01, d=0.75, 95%-CI [7.15, 30.54]) with large effect size. Confidence Intervals for all other indices range from negative to positive values and hence specify, that parameters were not systematically negatively affected in the first night. Findings suggest, that some individuals are more affected by the first-night effect than others. Yet, in order to keep the measurement uncertainties to a minimum, a more conservative approach with at least two monitoring nights should be used whenever possible, if no other supporting information on the athletes says otherwise.